Relation between inherent optical properties and land use and land cover across Gulf Coast estuaries. (19th February 2015) - Le, Chengfeng; Lehrter, John C.; Hu, Chuanmin; Schaeffer, Blake; MacIntyre, Hugh; Hagy, James D.; Beddick, David L.
Abstract Land use and land cover (LULC) can affect the watershed exports of optically active constituents such as suspended particulate matter and colored dissolved organic matter, and in turn affect estuarine optical properties. We collected optical data from six estuaries in the northeastern Gulf of Mexico with different watershed LULC characteristics and investigated how estuarine optical properties varied across these systems. Differences in LULC corresponded with significant differences in the estuarine inherent optical properties and specific inherent optical properties (SIOPs), which are known surrogates for phytoplankton cell size, organic particle concentration, and the amount of terrigenous dissolved organic carbon. The results indicated that increasing proportions of developed land use (urban + agriculture) in the watersheds resulted in a linear increase in light attenuation in the estuaries primarily through increased absorption by phytoplankton. Estuarine SIOPs were also linearly related to the proportion of developed land. These findings were used to demonstrate how improved knowledge of the factors regulating estuarine SIOPs may be used to increase the accuracy of semianalytical ocean color remote sensing algorithms in optically complex estuaries.